Tumors, Neurotransmitters and Pharmacology: Interactions and Implications - Abdelaziz GHANEMI (International Journal of Public Health Science (IJPHS), 2013)
Tumors represent a challenge for the modern therapies, and divers studies have shown that different factors are involved in both tumorigenesis and processes of tumor development. Therefore, further investigations and descriptions of inter-influences and interactions between the nervous system, the tumoral process and pharmacotherapies might lead to novel advances and applications, not only in the therapeutical approaches but also in the experimental design.DOI: http://dx.doi.org/10.11591/ijphs.v2i1.1831